2004
DOI: 10.1038/sj.npp.1300590
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Sequelae of Intravenous Amphetamine Self-Administration in Rats: Evidence for Selective Effects on Attentional Performance

Abstract: Characterizing the nature and severity of cognitive deficits associated with chronic stimulant abuse may provide new insights into the neural substrates of drug addiction because such deficits may contribute to the chronic relapsing nature of compulsive drug use. This investigation examines in rats the long-term cognitive consequences of intravenously self-administered amphetamine, specifically on performance of a 5-choice serial reaction time task (5-CSRTT), which assesses visuo-spatial attention and impulsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
64
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 54 publications
13
64
2
Order By: Relevance
“…However, a more likely reason is that in the five-choice serial reaction time task all trials are signal trials, in that animals are required to report the location of a brief visual stimulus. We also saw only a transient deficit on signal trials, and in this sense the results reported here are consistent with those reported by Dalley et al (2005aDalley et al ( ) (2005b.…”
Section: Percent Of Controlsupporting
confidence: 82%
See 1 more Smart Citation
“…However, a more likely reason is that in the five-choice serial reaction time task all trials are signal trials, in that animals are required to report the location of a brief visual stimulus. We also saw only a transient deficit on signal trials, and in this sense the results reported here are consistent with those reported by Dalley et al (2005aDalley et al ( ) (2005b.…”
Section: Percent Of Controlsupporting
confidence: 82%
“…First, it is important to emphasize that there were no group differences in omissions or response latencies in any of the experiments, suggesting that the animals were equally motivated to perform and did not suffer from obvious sensorimotor deficits. In contrast, in studies using the five-choice serial reaction time task, drugtreated animals did show a significant increase in omissions and response latencies, complicating interpretation of the nature of their deficit (Dalley et al, 2005a(Dalley et al, , 2005b. In addition, after the initial withdrawal period LgA animals' signal trial performance was normal, suggesting that the deficits are not attributable to a failure to retrieve the rules governing the responses in the two types of trials.…”
Section: Percent Of Controlmentioning
confidence: 76%
“…Interestingly, in the 5-CSRTT impaired attentional accuracy, increased omissions and slower latencies to respond has been observed following repeated withdrawal from self-administered amphetamine (Dalley et al, 2005b), cocaine or heroin (Dalley et al, 2005a). However, attentional performance deficits induced by these drugs of abuse were more pronounced and long-lasting than the deficits induced by nicotine in the present study and in that of (Shoaib and Bizarro, 2005).…”
Section: Discussioncontrasting
confidence: 53%
“…Repeated administration of psychostimulants has been shown to model important neurobiological, behavioral, and cognitive aspects of schizophrenia, including a sensitized mesolimbic dopamine system and impairments in attentional performance Goldman-Rakic, 1999, 2003;Castner et al, 2004Castner et al, , 2005Crider et al, 1982;Dalley et al, 2005;Featherstone et al, 2007;Fletcher et al, 2005Fletcher et al, , 2007Kapur, 2003;Martinez et al, 2005;Robinson and Becker, 1986;Russig et al, 2002;Tenn et al, 2003Tenn et al, , 2005. Based on extensive evidence indicating the crucial role of the cortical cholinergic input system for attention Parikh et al, 2007;Sarter et al, 2006Sarter et al, , 2005a, the attentional symptoms of schizophrenia have been proposed to be mediated via abnormalities in the regulation and activity of this neuronal system Raedler et al, 2003Raedler et al, , 2007Sarter et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%